The story of christianity 2000 years of faith - Collins, Michael; Matthew A. Price (London DK Limited, 2003)
From the Old Testament beginnings to contemporary worship, Christianity has a complex and controversial history. Covering topics as diverse as the early martyrs, the Crusades and the Reformation, this is an account of 2000 years of faith.
Keywords: Church history